The Translation of Nordic Workplace Democracy to the United States - Børve, Hege Eggen; Kvande, Elin (Nordic Journal of Working Life Studies, 2022)
This paper explores a translation process of Nordic workplace democracy by using an empirical case study of a Norwegian company setting up a subsidiary company in the US. The paper con- tributes to existing accounts of how ideas and practices in international companies are translated from one institutional context to another by focusing on the role of agency in translation processes. Drawing on advances in Scandinavian institutional theory, the findings show how employees from the source context acted as skilled translators in the new local context and helped to close the skills-gap between employees with and without experience of workplace democracy. In addition, the US managers had work experience from the company in Norway as well as from the US. The employees’ and managers’ complementary contextual knowledge represented important institutional bridging skills in the process of reproducing workplace democracy in the new local setting. However, during the translation process, some of the elements in the workplace democracy model were discussed and modified. This demonstrates how the organizations’ approach can change over time, from a reproducing to a modifying mode.